2007
DOI: 10.1080/00908310600626630
|View full text |Cite
|
Sign up to set email alerts
|

Extensional Viscosity of Polymer Based Fluids as a Possible Cause of Internal Cake Formation

Abstract: In this study, the effect of the rheology of viscoelastic fluids on the formation of internal filter cakes has been investigated. A series of core flow experiments have been conducted to investigate the possible relationship among the polymer concentration, fluid extensional viscosity, shear viscosity, filtration loss characteristics, and pressure drop across the core samples, and hence, any change in the original rock permeability. Results of extensional and shear viscosity measurements, API filtration loss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Therefore, both the extensional and shear viscosities influence the flow behavior of polymer solutions in porous media. The extensional viscosity could be the main reason for the extra pressure drop of polymer solutions in porous media (Durst et al, 1987;Navarrete et al, 2000;Khan et al, 2007). For a Newtonian fluid, the extensional viscosity is three times of the shear viscosity (Jones et al, 1987).…”
Section: Rheological Characterization Of 3 Wt% Polyethylene Oxide Somentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, both the extensional and shear viscosities influence the flow behavior of polymer solutions in porous media. The extensional viscosity could be the main reason for the extra pressure drop of polymer solutions in porous media (Durst et al, 1987;Navarrete et al, 2000;Khan et al, 2007). For a Newtonian fluid, the extensional viscosity is three times of the shear viscosity (Jones et al, 1987).…”
Section: Rheological Characterization Of 3 Wt% Polyethylene Oxide Somentioning
confidence: 97%
“…Saasen (1990) showed the influence of elastic modulus (G') and viscous modulus (G") on the flow of polymer-based fluids through porous media. Extensional deformation of fluid elements in porous media amplifies the elastic effects (Khan et al, 2007). Svendsen et al (1998) showed the establishment of internal filter cake by coiled tubing drilling fluid with high extensional viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…XG solutions have higher values of shear viscosity, extensional thinning and elongational viscosity than HPAM solutions, which can generate smaller volumes of filtered for XG solutions and less depth of invasion in the porous medium (Khan et al 2007). XG solutions have higher values of shear viscosity, extensional thinning and elongational viscosity than HPAM solutions, which can generate smaller volumes of filtered for XG solutions and less depth of invasion in the porous medium (Khan et al 2007).…”
Section: Conceptsmentioning
confidence: 99%
“…Most commonly used EOR polymers are HPAM and are particularly sensitive to mechanical degradation (W. Littmann, 1988). Khan et al (2007) explained the elastic effects of extensional deformation of fluids in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly used EOR polymers are HPAM and are particularly sensitive to mechanical degradation (W. Littmann, 1988). Khan et al (2007) explained the elastic effects of extensional deformation of fluids in porous media. Detailed explanation of mechanism of chemical/mechanical and biological degradation of different polymers is given elsewhere (Sorbie, 1991) (Heemskerk et al, 1984).It is of prime importance to know the degradation behavior of polymers used in any polymer flood process.…”
Section: Introductionmentioning
confidence: 99%